Proper Assessment of Learning Materials Based Interactive Multimedia According to Expert Validator of Materials in Class 10th of Tritech Informatika Vocational School Medan, Learning Year 2017/2018, Indonesia - Wan Anisa Maulidya Baros; Mutsuhito Solin; Isda Pramuniati (BIRCU, 2019)
Learning activities include developing teaching materials that are carried out to respond to students so that they are more interested in learning that will be associated with current technological developments. One product of technology that can be used to develop teaching materials for the learning process is interactive multimedia which is a combination of various media in the form of text, graphics, audio, and interactions that are used to convey information messages from sender to receiver equipped with a controller which can be operated by the user. Efforts can be made to make learning effective one of which is the use of multimedia in interactive learning. Learning by using multimedia will be more interesting, more effective, efficient learning time, improve the quality of learning so that the objectives of a learning activity can be achieved. The purpose of this research is to improve learning outcomes, including improving aspects development research related to learning activities including developing teaching materials to respond to students to be more interested in learning that will be associated with current technological developments. This research method is development research (Research and Development) which is a study used to produce certain products and test the effectiveness of these products. The researcher found a method in interactive teaching in using multimedia as an improvement in the quality of students' loyalty in the classroom.